Two new records of Hydrochidae (Coleoptera) species from Turkey, with some ecological notes - Incekara, Ümit; Mart, Abdullah; Erman, Orhan (My University, 2004)
Two newly recorded Hydrochus Leach, 1817 (Coleoptera, Hydrochidae) species for the Turkish fauna, Hydrochus ignicollis (Motschulsky, 1860) and H. brevis (Herbst, 1793), are described and some ecological notes and their distribution in Turkey and worldwide are presented. © TÜBITAK.
Keywords: Coleoptera; Hydrochidae; Hydrochus; Systematics; Turkey